Altered adenosine-to-inosine RNA editing in human cancer - Paz, Nurit; Levanon, Erez Y.; Amariglio, Ninette; Heimberger, Amy B.; Ram, Zvi; Constantini, Shlomi; Barbash, Zohar S.; Adamsky, Konstantin; Safran, Michal; Hirschberg, Avi; Krupsky, Meir; Ben-Dov, Issachar; et al.

(untitled) (Genome Research, 2007)
Adenosine-to-inosine (A-to-I) RNA editing was recently shown to be abundant in the human transcriptome, affecting thousands of genes. Employing a bioinformatic approach, we identified significant global hypoediting of Alu repetitive elements in brain, prostate, lung, kidney, and testis tumors. Experimental validation confirmed this finding, showing significantly reduced editing in Alu sequences within MED13 transcripts in brain tissues. Looking at editing of specific recoding and noncoding sites, including in cancer-related genes, a more complex picture emerged, with a gene-specific editing pattern in tumors vs. normal tissues. Additionally, we found reduced RNA levels of all three editing mediating enzymes, ADAR, ADARB1, and ADARB2, in brain tumors. The reduction of ADARB2 correlated with the grade of malignancy of glioblastoma multiforme, the most aggressive of brain tumors, displaying a 99% decrease in ADARB2 RNA levels. Consistently, overexpression of ADAR and ADARB1 in the U87 glioblastoma multiforme cell line resulted in decreased proliferation rate, suggesting that reduced A-to-I editing in brain tumors is involved in the pathogenesis of cancer. Altered epigenetic control was recently shown to play a central role in oncogenesis. We suggest that A-to-I RNA editing may serve as an additional epigenetic mechanism relevant to cancer development and progression.